(Re)Territorialização da estratégia saúde da família em Uberlândia: ações a partir do território de vida seus fixos e fluxos - Alves, Marlúcio Anselmo (2014)
The central goal of this research is to identify the best approach of the territory for use by the ESF, in Family Basic Units of Strategy of Health Parque São Jorge I and Parque São Jorge II. It is understood that the study would subsidize future implementations of teams and restructuring of those already existing. The main purpose is to reread the territories covered and use them for the Health Promotion. In this way, this research hypothesis is that the actions of ESF it s not being effectives in the way to attend these assumptions, what it means to reduce the incidence of use of the other levels of attention with actions of prevention and Health Promotion, because of the inadequate approach and little use of territory in health actions. The research was guided by the bibliographic and documental revision by the database of the library and thesis database of UFU, thesis portal of CAPES, library and database of the Universidade de Lisboa (University of Lisbon), publications in the online library database LILACS, BVS, OPAS, IBGE data, SIAB, DATASUS among others. The field research occurred in the period from January to December of 2013 and from January to February of 2014, whereas the access to ESF data only occurred after the approbation of the Internship and Research Sector of the Municipal Prefecture of Uberlândia. For the performance of this research, was done reading the territory to diagnose the scenario and detect the merits and weaknesses for the health promotion in this place. In this case was elected elements from the perspective of having a broader view of health. To this was considered the territory like an open system, dynamic and complex; analyzed in multiscale form. The approach of this fragilities and potentialities occurred inside the Miltonian view of fixes and flows of the territory located in maps and identified according to the greater or lesser potential health risks, as well as the locus of opportunity to the practice of the ESFs of actions with the community within the health district.